2014
DOI: 10.1177/1533317514549650
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Health Condition in Patients With Alzheimer’s Disease

Abstract: The periodontal health status of individuals with AD deteriorates with disease progression and was closely related to their cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 28 publications
(34 reference statements)
3
116
2
3
Order By: Relevance
“…Two previous studies reported that periodontitis was related to cognitive decline and disease progression in patients with Alzheimer-type dementia [77,78]. However, our study is the first to indicate an association between chronic periodontitis and gingivitis, and the risk of dementia in a nationwide, population-based study.…”
Section: Discussioncontrasting
confidence: 46%
“…Two previous studies reported that periodontitis was related to cognitive decline and disease progression in patients with Alzheimer-type dementia [77,78]. However, our study is the first to indicate an association between chronic periodontitis and gingivitis, and the risk of dementia in a nationwide, population-based study.…”
Section: Discussioncontrasting
confidence: 46%
“…Another mechanism proposed as being a contributing factor for developing cognitive impairment is the presence of oral infections, such as periodontitis. Martande et al reported a higher incidence and severity of periodontitis in patients with AD 56 . Periodontal pathogens could provide inflammatory mediators due to daily, transient bacteremias, which in return increase the oxidative stress in Alzheimer's disease (AD) 57 .…”
Section: Cognitionmentioning
confidence: 95%
“…They were conducted in 5 different countries across Europe [10,12] , North [26] and South America [27] , and Asia [11] , and were published between 1994 and 2015 ( Table 1 ). The population sample ranged from 42 patients in the study by Ship and Puckett [26] to 409 patients in the study by Gil-Montoya et al [12] 2 of the studies were cross-sectional [10,11] , 2 were case-control [12,27], and one was a longitudinal observational study [26] .…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…In the previous years, there has been an increase in the publication of literature in order to investigate the possible association between PD and AD, with heterogeneous results [10][11][12] . Despite the existence of numerous narrative reviews [8,9,[13][14][15][16] , the use of subjective and non-standardized methods may have led to bias [17] .…”
Section: Introductionmentioning
confidence: 99%